Bird droppings on chestnut leaves or sawfly larvae: DNA barcodes verify the occurrence of the archaic Megaxyela togashii (Hymenoptera, Xyelidae) in Hokkaido, Japan - Shinohara, Akihiko; Hara, Hideho; Kramp, Katja; Blank, Stephan M.; Kameda, Yuichi (Zootaxa, 2017)
We made a molecular phylogenetic analysis using mitochondrial cytochrome oxidase subunit 1 (COI) gene sequences for ten unidentified Megaxyela larvae from Hokkaido, Honshu and Shikoku, Japan, and 15 identified adults of four Megaxyela, one Macroxyela and three Xyela species. It revealed that all larvae belonged to M. togashii Shinohara, 1992, which showed rather large intraspecific genetic variability even among the individuals from the same population. This is the first distribution record of M. togashii from Hokkaido. Megaxyela togashii is a univoltine species with a very short larval feeding period, only nine days in one rearing experiment from egg to larval maturation. The larva is a solitary, external leaf-feeder on Juglans ailanthifolia, resting curled around the central leaf vein at the apex of a leaflet, and may resemble the excrement of birds. The prepupa overwinters in an earthen cell whose wall is made only of soil, neither parchment-like nor containing fiber. The mature larva is described and several life traits are discussed.